Penerapan Perjanjian Jual Beli Online di Aplikasi Shopee Berdasarkan KUHPERDATA Dan UU ITE - Choiril Ilham, Priambudi; Saputra, Arikha (UNES Law Review, 2023)
One of the e-commerce that is often used is shopee. In online shopping consumers decide to buy a product with the best reviews. However, in reality, the best rating cannot guarantee that violations will not occur. This could have happened due to the negligence of the seller, user, or expeditionary party. For this reason, Shopee is required to provide assurance regarding online buying and selling agreements and the claim mechanism for these violations in accordance with the Civil Code and Law Number 19 of 2016 concerning ITE. This type of research is normative juridical research with descriptive analytical research methods. Analysis is carried out to obtain clear, systematic and detailed results. The research results in the online sale and purchase agreement must comply with the provisions for effective communication, personal data protection, compliance with consumer protection, use of good policies and procedures, contractual responsibility, timely refunds, and compensation for losses. The mechanism for the claim process carried out by the shopee party in violation of the online buying and selling agreement at shopee is carried out on the principle of good faith, which is the implementation of the UUPK.